Urban pedagogies and the celling of adolescents of color - Duncan, Garrett Albert (Social justice, 2000)
Part of a special issue on critical resistance to the prison-industrial complex. The writer examines the relationship between the economy, society, and school in order to assess the role of public education in the growing prison-industrial complex. He argues that the primary aim of urban public schools in the lives of students of color has been to prepare them to occupy and accept subordinate roles within the U.S. economy and society. He also contends that urban pedagogies effectively serve the economic function of moving colored young Americans into the prison system.